Nanostructured Co-doped BiVO4 for efficient and sustainable photoelectrochemical chlorine evolution from simulated sea-water - Chauhan, Inderjeet; Patra, Kshirodra Kumar; Bajpai, Himanshu; Mhamane, Nitin B.; Salgaonkar, Kranti N.; Gopinath, Chinnakonda S. (Dalton Transactions, 2023)
The co-production of hydrogen and chlorine from sea-water splitting could be a potential, sustainable and attractive route by any method. However, challenges to overcome are many, and critically, the sustainability and operating potential of the electrocatalyst are important. In this work, we report on Co-doping in the BiVO4 (Co-BV) crystal lattice and employed the same as the photoanode; Co-BV exhibits a photocurrent of 190 mu A cm(-2) at 1.1 V vs. RHE (the reversible hydrogen electrode) in the acidic sodium chloride solution (pH 2.3) under one sun illumination. The best-performing photoanode, with 0.05 mol% of Co doping (0.05 Co-BV), selectively produced active chlorine with 92% faradaic efficiency at 1.1 V vs. RHE by successfully suppressing the kinetically sluggish oxygen evolution reaction (OER) and the stability of the catalyst was demonstrated for up to 20 h. This is the lowest operating potential reported for the chlorine evolution reaction (CER), thus far. The overpotential required for CER with 0.05 Co-BV is lower than that of OER, which leads to selective CER at 1.1 V (vs. RHE). Co-doping into the BiVO4 lattice decreases the charge transfer resistance and enhances the CER kinetics due to its structural and electronic integration with the BV lattice. We demonstrate that Co-doping also improves the lifetime of the charge carrier and enhances the current density of CER and sustainability of the catalyst.